Military Migrants : Fighting for YOUR Country. - Ware, Vron (Migration, diasporas and citizenship., 2012)
This is the first book to examine ""migrant-soldiers' in the British army and places the phenomenon of Britain's multicultural army in relation to British culture, history and nationalism. It also explores the impact of war on UK society during the 21st Century.